Skeletal muscle architectural adaptations to marathon run training - Murach, K.; Greever, C.; Luden, N. D. (Applied Physiology, Nutrition, and Metabolism, 2016)
We assessed lateral gastrocnemius (LG) and vastus lateralis (VL) architecture in 16 recreational runners before and after 12 weeks of marathon training. LG fascicle length decreased 10% while pennation angle increased 17% (p < 0.05). There was a significant correlation between diminished blood lactate levels and LG pennation angle change (r = 0.90). No changes were observed in VL. This is the first evidence that run training can modify skeletal muscle architectural features.